Factor Analysis of Service Quality in Pearl Milk Tea Beverage Businesses of Generation Y in Bangkok - Panitchaikul , Paweena; Chankoson, Thitinan (KKBS Journal of Business Administration and Accountancy, 2020)
The purpose of this research is to analyze factor of service quality in pearl milk tea beverage businesses of generation Y in Bangkok by using the quantitative research methodology. The samples were generation Y consumers four hundred who bought pearl milk tea drinks. The data were collected by using questionnaires. The statistics used for data analysis were frequency, percentage, mean and exploratory factor analysis (EFA). The results of this research were as follows: The analysis’s result of exploratory factor analysis: Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO) = 0.878 and Bartlett’s Test of Sphericity as Chi-Square = 34192.093, df= 630. The factor extraction by using EFA indicated that the five factors including purity (P), experience (E), agility (A), resolution (R), and level of service (L), respectively. These could be interpreting 78.62 % of variance.